C5a Induces Tissue Factor Activity on Endothelial Cells - Ikeda, Kei; Nagasawa, Kohei; Horiuchi, Takahiko; Tsuru, Tomomi; Nishizaka, Hiroaki; Niho, Yoshiyuki (Thrombosis and Haemostasis, 1997)
Tissue factor (TF) is an integral membrane glycoprotein that serves as a cofactor for blood coagulation factor VIIa. The induction of TF on the surface of endothelial cells is initiated by various stimuli including lipopolysaccharide, interleukin-1β, and tumor necrosis factor α. We have demonstrated that recombinant human C5a induces TF activity in a dose-dependent fashion in human umbilical vein endothelial cells (HUVEC). Peak activity (4.9-fold increase) was obtained 3-6 h after treatment with 10 μM C5a. TF mRNA as assessed by RT-PCR method was also significantly increased (3.75-fold) after 3 h incubation with C5a, suggesting that C5a induces TF activity on HUVEC, at least in part, by enhancing the level of TF mRNA. The increase in TF activity by C5a was inhibited by methylprednisolone. The induction of TF on endothelial cells by C5a may represent one of many potential interrelationships between the inflammatory and coagulation schemes.